THE FUNCTIONS OF THE VERB PARADIGMS WITH IMA ‘HAVE’ AND N/T PARTICIPLE IN THE VELES DIALECT (Journal of Contemporary Philology, 2022)
The verbal system of the Macedonian language is one of the most complex among the Slavic languages. On the one hand, the inherited Slavic characteristics are preserved in the structure of the Macedonian language, but, on the other hand, it has incorporated features motivated by the direct contact with the Balkan non-Slavic languages. Macedonian is the only Slavic language that has incorporated periphrastic constructions with ima ‘have’ and n/t participle as regular paradigms. These constructions participate in a number of temporal paradigms, especially in the system of past tenses. In addition, Macedonian did not reject theinherited Slavic perfect constructions with sum ‘be’ and l-participle, but moved them into the modal sphere of use. The ‘have’ perfects, which originated in the southern and western parts of the Macedonian dialect area, are spreading from the southwest to the northeast. In this paper, the author analyzes the paradigms with ima and n/t participle in the speech of Veles, as part of the central group of the western Macedonian dialect. The analysis shows that the grammaticalization of these constructions has advanced in the Macedonian speech of Veles, and their sphere of use is still expanding.
Keywords: Macedonian language; Veles dialect; ima-constructions; perfect; plusquamperfect